NON-CHURCH ICONS – THE SPIRITUAL CENTER OF PROFANE SPACE - Hoshovskyy, R. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
First a role and features of introduction of no temple icons turns out in the wide circle of profan interiors of end ХХ – beginning of ХХІ age. Traditions of old domestic icon and its influence on modern room and office icons are determined.